Integrated Marketing Communication To Enhance Active User of Internet Banking Service: Case Study Bank XYZ - Prawitasari, Larasati; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2012)
Internet banking is a form of self-service technology. In the global banking business, Internet banking has a big role for doing the business. In developing country, Internet banking received relatively little attention although has been deployed for years. Only 3% of customer Bank XYZ in Indonesia using Internet banking service actively, although has been 9 years Bank XYZ introduced Internet banking service. This study addressed what factor that drives and influences Internet banking acceptance, why Internet banking does not seems quite attractive to customer and how banks manage their Internet banking. SWOT analysis of Bank XYZ and customer toward Internet banking service is mapped in order to see the connection between them and determine the root causes. The alternative solution for Bank XYZ problem is a marketing communication strategy to educate the customer about the importance of doing transaction through internet banking which is easy and practical. The approaching concept to develop marketing communications programs are Interest, Search, Action, Share, and Loyal. Some alternative programs are developed based on that approach concept. At the end there are two scenarios of recommended program. The implementation of the recommended program as the business solution, formed in an activity planning schedule and human resources needed for each recommended scenarios.Keywords: Bank, Internet Banking, Integrated Marketing Communication